2021
DOI: 10.3390/jmp2010003
|View full text |Cite
|
Sign up to set email alerts
|

Collection and Handling of Thoracic Small Biopsy and Cytology Specimens for Ancillary Studies: Guidelines from the College of American Pathologists (CAP)

Abstract: With a growing number of clinically relevant biomarkers needed to guide the management of patients with non-small cell lung cancer (NSCLC), pathologists are keenly aware of the need to collect adequate tissue not only for a diagnosis, but also for ancillary studies to provide predictive and prognostic information. Small specimens collected by minimally invasive techniques such as fine needle aspiration and core needle biopsy often fall short in meeting adequacy requirements for lung cancer molecular biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The shorter procedure time afforded by realtime CT, often referred to as "CT fluoroscopy, " creates time for ROSE and the collection of additional samples [32]. A minimum of at least four tissue cores was recommended by the panel, exceeding the minimum of three recommended by the CAP guideline since research has demonstrated that sensitivity for histopathologic diagnosis and molecular testing increases significantly between the second and fourth samples [24,[33][34][35]. ROSE remains best practice according to the literature [36], despite the limitations noted by the panel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shorter procedure time afforded by realtime CT, often referred to as "CT fluoroscopy, " creates time for ROSE and the collection of additional samples [32]. A minimum of at least four tissue cores was recommended by the panel, exceeding the minimum of three recommended by the CAP guideline since research has demonstrated that sensitivity for histopathologic diagnosis and molecular testing increases significantly between the second and fourth samples [24,[33][34][35]. ROSE remains best practice according to the literature [36], despite the limitations noted by the panel.…”
Section: Discussionmentioning
confidence: 99%
“…FNA was generally not performed but may have a role in facilitating ROSE [37]. However, touch preparations of tissue cores offer an alternative to ROSE based on fine needle aspirates, and use of touch preparations is supported by the CAP guidelines on handling lung needle biopsy specimens [24]. Limiting the need for re-biopsy was a valid concern among radiologists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as many as 40%–70% of all advanced NSCLC are diagnosed by cytological evaluation alone, with no concurrent histological examination of tissue material, emphasising the necessity to expand ALK and ROS1 analysis to cytological specimens. 9 10 48–51 …”
Section: Alk and Ros1 Analysis In Cytolog...mentioning
confidence: 99%
“…In relation to the optimal sample and its handling, in addition to the paraffined material (tissue samples or cell blocks from cytological samples), cytological extensions can be used. 9 The use of protocols for tissue utilisation that allow both the pathological diagnosis and biomarker assays were recommended. 6 15 16 …”
Section: Updated Guidelines For Selection Of Biomarkersmentioning
confidence: 99%